Comparison of acute toxicities between contemporary forward‐planned 3D conformal radiotherapy and inverse‐planned intensity‐modulated radiotherapy for whole breast radiation. Issue 2 (13th July 2017) - Guttmann, David M.; Gabriel, Peter; Kennedy, Christopher; Rate, William; Grizos, William; Nagda, Suneel; Wojtowicz, Lisa; Lin, Lilie; Freedman, Gary M.
Abstract: The use of inverse‐planned intensity‐modulated radiation therapy for whole breast radiation treatment has become more prevalent, but this may impose an increased cost on the health system. We hypothesized that when applied with the same treatment planning goals, tangential forward‐planned field‐in‐field 3D conformal radiotherapy and tangential inverse‐planned intensity‐modulated radiotherapy would be associated with comparable toxicities. Women who underwent tangential whole breast irradiation at our institution from 2011 to 2015 planned using either forward‐planned field‐in‐field 3D conformal radiotherapy or intensity‐modulated radiotherapy were retrospectively analyzed. Grade 2+ Radiation dermatitis was the primary endpoint. A total of 201 and 212 women had undergone field‐in‐field 3D conformal radiotherapy and intensity‐modulated radiotherapy, respectively. No differences were observed between the two modalities regarding acute radiation dermatitis, breast pain, or fatigue. In a multivariable logistic regression that incorporated the use of boost, hypofractionation, use of chemotherapy, patient positioning, use of a supraclavicular field, and breast planning target volume, intensity‐modulated radiotherapy was not correlated with different rates of Grade 2+ radiation dermatitis. This study supports the routine first‐line use of field‐in‐field 3D conformal radiotherapy for whole breast radiation instead of tangential intensity‐modulated radiotherapy from the standpoint of equivalence in acute toxicity. Further investigation is needed to assess whether there are subgroups of women who may still benefit from intensity‐modulated radiotherapy.